Kontribusi Pesantren Ma’had Dar Al-Qur’an Wa Al-Hadith (MDQH)Al-Majidiyah Al-Shafiiyah Nahdlatul Wathan dalam Merawat Tradisi Ketuan-Guruan di Lombok, NTB - Muslim, Supratman; Suprapto; Jamaluddin (Religion, Culture, and State Journal, 2021)
Pesantren is a religious educational institution whose existence has a long history in Indonesia. Pesantren has an important role in producing religious figures including kyai, ulama and tuan guru. However, this role began to fade as many secular educational institutions emerged which were marked by the presence of modernization in various fields, and at the same time pesantren began to change a lot to adapt to this new system and structure. This study specifically aims to explore the role and contribution of Pesantren Ma'had Dar Al-Qruan wa Al-Hadis (MDQH) Nahdlatul Wathan in defending the reproduction of tuan guru tradition, and strategies are used to be able to maintain this tradition. This research also focuses on examining the continuity and change that occurs and is carried out by MDQH NW in reproducing the tuan guru tradition. This study uses qualitative methods in data collection and analysis. In terms of collecting data, researchers used some techniques including observation-participation, in-depth interviews and documentation in data collection. The theory used to analyze the data in the field is social capital theory, to see the network that is built and the trust that MDQH teachers continue to instill in students, parents and the surrounding community. The results showed that MDQH NW had a significant contribution in maintaining the tuan guru tradition. This is evidenced by the pattern of education and all institutional activities oriented to the pesantren culture with the study of the al-Mu'tabarah book in the halaqah system. The strategies used include strengthening traditional education strategies, socio-religious relations, and Islamic da'wah. Continuity is also seen in the social relations built with the community at Madrasah Shaulatiyah Makkah al-Mukarromah and the collaboration between institutions. The changes that occur in MDQH NW Pancor are in the volume of study time, especially for female students (talibat) who previously took 3 years to 4 years, equated with male students (tullab). However, pesantren MDQH NW in Anjani still maintains the provisions that became the legacy of its founders, namely 3 years for lalibat and 4 tullab.